Vollnomaden und Halbnomaden im Steppenhochland und in der nördlichen Sahara: Wirtschafts- und sozialgeographische Umrisse und Wandlungen - Niemeier, Georg (ERDKUNDE, 1955)
The nomadic forms of life in French North Africa are changing under the increasing pressure from modern civilization, together with the effect of weather catastrophes which occurred after both world wars. Also dianging are the economic bases and social structures of the nomads. It is thus obvious that the different modes of life cannot be „explained simply by reference to the physical character of the country, despite the elementary and prominent nature of many relationships, especially to climatic conditions. A distinction can be made, according to their mode of life, between full and semi-nomads and, according to the point of gravity of their habitat, between desert, steppe and mountain nomads. The basic economy and life of the desert nomads of Chaâmba Berezga, together with recent changes, is given in detail. Further examples show variations and transitional forms, as follows: the desert camel nomads of Reguéibat Lgouacem; transition to seminomadism in the interior parts of the Sahara; migration of desert nomads to the highland steppe, and the cutting down of their best pasture grounds as a result of the French colonization and extension of cultivation by nomads themselves. The great variety of the semi-nomadic modes of life and economy in the highland steppe and its surrounding mountains is explained largely by the differentiation of the habitat into sub-regions and their location with respect to the Tell area and its various attractions of modern civilization. This results in a tendency towards cultivation, the disruption of the communal economy and the larger social groups, the private and individual appropriation of land, and the individualisation and often prolétarisation of the modes of life. The French administration has improved the living conditions in various ways, as for instance through pacification, boring of artesian wells, building of roads, introducing a health service, schools and new possibilities of gaining a livelihood. But, inspite of this, the primary production, be it animal husbandry or arable cultivation, has been unable to keep pace with the population growth, and there are not sufficient openings in other occupations to provide a living for all. Document Actions